Intergral from -2 to 2 (-2 is at the bottom of the integral sign and 2 is at the top) x^-2dx = -x^-1] (the bracket has a 2 at the top and -2 at the bottom) = -(2)^-1-(-(-2)^-1) = (-1/2)-(1/2) = -1
Is this true or false. I think it's false, but can someone explain to me why it's false.
CALCULUS HELP PLEASE!! - Reiny, Thursday, May 12, 2011 at 7:48am
The question is done correctly.
When you differentiate
-x^-1 you get x^-2
and all the arithmetic was done correctly.
If this an "area between curves" type, I have seen this before.
The function f(x) = 1/x^2 is discontinuous at x=0
so even though calculation-wise we come up with the answer above, it would be meaningless.
CALCULUS HELP PLEASE!! - Mgraph, Thursday, May 12, 2011 at 2:53pm
The answer is wrong because function x^(-2)>0 on [-2,2] except x=0 =>integral>0
This is Improper integral which is divergent.
x^(-1)-->infinity if x-->0